Paresthesia of nerve due to acute apical periodontitis of a non-vital tooth: report of two cases - Mojtahed Bidabadi, Maryam; Ashraf, Hengameh; Arjmand Inaloo, Pejman; Darmiani, Soheila (International Journal of Dental Research, 2014)
Paresthesia or dysesthesia of the inferior alveolar nerve (IAN) as the result of endodontic treatment or periodontal disease is a rare but serious occurrence. This paper describes two cases of paresthesia and dysesthesia of the IAN due to acute apical periodontitis of a right mandibular second molar and a right mandibular second premolar in proximity to inferior alveolar canal. Symptoms of sensory disruption disappeared approximately 2 months after conventional endodontic treatment associated with antibiotic therapy. One year later both teeth were still asymptomatic. Keywords: Endodontic Pain, Inferior Alveolar Nerve, Injuries, Paresthesia.